Differential Expression of Ly6C and T-bet Distinguish Effector and Memory Th1 CD4 + Cell Properties during Viral Infection - Marshall, Heather D.; Chandele, Anmol; Jung, Yong Woo; Meng, Hailong; Poholek, Amanda C.; Parish, Ian A.; Rutishauser, Rachel; Cui, Weiguo; Kleinstein, Steven H.; Craft, Joe; Kaech, Susan M. (Immunity (Cambridge, Mass.), 2011)
CD4 + T cells differentiate into multiple effector types, but it is unclear how they form memory T cells during infection in vivo. Profiling virus-specific CD4 + T cells revealed that effector cells with T helper 1 (Th1) or T follicular helper (Tfh) cell characteristics differentiated into memory cells, although expression of Tfh cell markers declined over time. In contrast to virus-specific effector CD8 + T cells, increased IL-7R expression was not a reliable marker of CD4 + memory precursor cells. However, decreased Ly6C and T-bet ( Tbx21) expression distinguished a subset of Th1 cells that displayed greater longevity and proliferative responses to secondary infection. Moreover, the gene expression profile of Ly6C loT-bet int Th1 effector cells was virtually identical to mature memory CD4 + T cells, indicating early maturation of memory CD4 + T cell features in this subset during acute viral infection. This study provides a framework for memory CD4 + T cell development after acute viral infection. [Display omitted] ► Increased IL-7R expression does not mark CD4 + memory precursor cells ► T-bet acts in a graded manner to regulate formation of Th1 and Tfh cell subsets ► Ly6C loT-bet int Th1 effector CD4 + cells have enhanced longevity and recall responses ► Ly6C loT-bet int Th1 effector and memory CD4 + cells share similar gene expression